BOOK HERITAGE OF VASA DYNASTY IN VILNIUS UNIVERSITY LIBRARY - MACIULEVIČIUS, ARVYDAS (Knygotyra, 2012)
On the basis of the specimens which include the super ex-libris of the House of Vasa stored at the Rare Book Department of Vilnius University Library, the article attempts to answer the question whether the books might be attributed to the House of Vasa. The question is solved with reference to the analogues of the collection of books belonging to the House of Vasa stored in the libraries in Poland, Sweden and Germany. In addition to the major question, the article recreates the representation of the cultural life in the palace, analyses the relationship between the monarchs and a book, discusses the ways a book would reach the palatial library, highlights the topic of the collection of the books and shows their fate.The comparative analysis of the books stored in Vilnius and their analogues in Poland, Sweden and Germany enables the conclusion that they might be attributed to the House of Vasa. Although the provenances pertain to different persons, they do not deny that the aforementioned books most likely belonged to the library of Wladysław Vasa. Of course, a more substantial attribution requires more comprehensive research, the present article is expected to encourage.
Keywords: ...